Curso / taller ensamblaje, mantenimiento y revisión de pc´s, una alternativa de trabajo para las zonas urbano-marginales. - Macias Coello, Jorge Luis (2009)
The Workshop on Assembly, Maintenance, and Testing of PC´, was built in order to help develop small low income sectors. The main goal of this work was to give a chance to outside urban communities to carry out an activity that allows them to get an income with their own work becoming productive entrepreneurs. After completion of the process, students will be able to execute tasks related to computers, such as, assembling PC components and Hardware, or doing some preventive maintenance on Hardware and Software. A brief guide has been designed in order to show in a detailed way the processes of selection, teaching, and evaluation. Each section goes through reflections about attitudes and skills required for being a selected for the program. The guide also includes detailed findings made during the tutoring process, and results gotten at the end of the course, based on a framework matrix designed before starting classes. Using this matrix, students gave feedback regarding the process, by indicating the value or the potential value of this project.